A survey and analytical approach on image compression for DICOM Images - Baraskar, TN; Mankar, VR (International Journal of Computer Sciences and Engineering, 2025)
As medical imaging move towards digital imaging, medical information compression play major role in tele radiology application development. A DICOM standard work as an interface to send data from vendor independent equipment (Picture archiving and Communication System) to PDA based tele radiology system. With the help of DICOM file format, radiologist can view images in different file format. For excessing, viewing and examining patient information and images, information transmission and compression are key issues in case of such platform usage. This Paper served information of available compression techniques like Lossy and Lossless, JPEG, JPEG-LS, JPEG2000. The propose paper also analyze and compare different lossy and lossless techniques based of domain, principle and methods used. This paper contributed information related to Image Hierarchical Coding and there types like Bit Planes, Tree Structure, Laplacian Pyramid, Gaussian Pyramid. The paper also include comparison of different Wavelet family and Wavelet Transform based on various parameters.